Effect of L-carnitine on lipid biomarkers of oxidative stress in chronic hemodialysis patients: a randomized controlled trial - Shokoh Shayanpour; Seyyed Seyfollah Beladi Mousavi; Hossain Karimpourian; Khojasteh Hoseinynejad; Kambiz Ahmadi Angali (Gazi Medical Journal)
Objective: This clinical trial aimed to evaluate the effect of L-carnitine on serum levels of lipid biomarkers of oxidative stress in chronic hemodialysis patients. Methods: From a total of 90 patients with end-stage kidney disease enrolled in this trial, 87 patients completed the study. L-carnitine tablets (250 mg/T) dissolved in 30 mL water (25 mg/kg) were administered orally twice daily before meals for a period of 3 months in the intervention group (n=44). Instead, the controls (n=43) received placebo. Before and 12 weeks after treatment, serum levels of malondialdehyde (MDA), low-density lipoprotein (LDL), and other markers were measured. Results: The mean serum levels of MDA after hemodialysis (before L-carnitine therapy) were respectively 5.64±2.04 and 5.78±2.12 μmol/L in the intervention and control groups, respectively, which were not statistically different from the levels before hemodialysis (5.60±2.05 and 5.74±2.16 μmol/L, respectively, p>0.05). The reduction in MDA levels after L-carnitine therapy was significantly greater in the intervention group vs. controls (5.17±2.04 vs. 5.60±2.13 μmol/L, p<0.001). In addition, the reduction in LDL levels after treatment was significantly more evident in the intervention group compared with that in the controls (p<0.001). The dose consumption of erythropoietin decreased far more in the intervention group (from; 8000±520 to 3750±418 unite/week) than in the control group (from; 8000±318 to 6000±528) after 5 months of follow-up (p=0.029). Conclusion: Oral administration of L-carnitine in chronic hemodialysis patients may remarkably modulate lipid marker levels of oxidative stress and reduce the dose consumption of erythropoietin without any side effects.